We are going to learn in this chapter a new concept, i.e., dividing a term by another term with same exponent.Let us solve the examples :

- (8/3)
^{3} - (5/7)
^{4}

In the first example, i.e., (8/3)^{3} can be written as (8/3) x (8/3) x (8/3), again can be written as

(8 x 8 x 8) / (3 x 3 x 3), according to the law can be written as 8^{3} / 3^{3}.

Therefore we get the result for (8/3)^{3} as 8^{3} / 3^{3}.

Coming to second example, i.e., (5/7)^{4} can be written as (5/7) x (5/7) x (5/7) x (5/7), again can be written as (5 x 5 x 5 x 5) / (7 x 7 x 7 x 7), according to the law can be written as 5^{4} / 7^{4}.

Therefore we get the result for (5/7)^{4} as 5^{4} / 7^{4}.

Let us try to solve few more examples :

- (7/4)
^{5} - (a/b)
^{m} - (5/7)
^{3}

In the first example, ie., (7/4)^{5} = (7/4) x (7/4) x (7/4) x (7/4) x (7/4)

= (7 x 7 x 7 x 7 x 7) / (4 x 4 x 4 x 4 x 4)

= 7^{5} / 4^{5.}

Therefore the result for (7/4)^{5} = 7^{5} / 4^{5}.

Coming to second example, i.e., (a/b)^{m} = (a/b) x (a/b) x …. m times

= (a x a x … m times) / (b x b x … m times) times

= a^{m} / b^{m}.

Therefore the result for (a/b)^{m} = a^{m} / b^{m}.

In the last example, i.e., (5/7)^{3} = (5/7) x (5/7) x (5/7)

= (5 x 5 x 5) / (7 x 7 x 7)

= 5^{3} / 7^{3}

Therefore the result for (5/7)^{3} = 5^{3} / 7^{3}.

In the examples, (a/b)m = am/bm concept is used. |

The examples are been illustrated in the video below :